CYP2A6 Longitudinal Effects in Young Smokers - Cannon, Dale S. (Nicotine Tob Res, 2016)
INTRODUCTION: The present study sought to identify time-dependent within-participant effects of CYP2A6 genotypes on smoking frequency and nicotine dependence in young smokers. METHODS: Predicted nicotine metabolic rate based on CYP2A6 diplotypes (CYP2A6 diplotype predicted rate [CDPR]) was partitioned into Normal, Intermediate, and Slow categories using a metabolism metric. Growth-curve models characterized baseline and longitudinal CDPR effects with data from eight longitudinal assessments during a 6-year period (from approximately age 16–22) in young smokers of European descent (N = 296, 57% female) who had smoked less than 100 cigarettes lifetime at baseline and more than that amount by Year 6. Phenotypes were number of days smoked during the previous 30 days and a youth version of the Nicotine Dependence Syndrome Scale (NDSS). A zero-inflated Poisson growth-curve model was used to account for the preponderance of zero days smoked. RESULTS: At baseline, Intermediate CDPR was a risk factor relative to both Normal and Slow CDPR for smoking frequency and the NDSS. Slow CDPR was associated with the highest probability of smoking discontinuation at baseline. However, due to CDPR time trend differences, by young adulthood these baseline effects had been reordered such that the greatest risks for smoking frequency and the NDSS were associated with Normal CDPR. CONCLUSIONS: Reduced metabolism CYP2A6 genotypes are associated with both risk and protective effects in novice smokers. However, differences in the time-by-CDPR effects result in a reordering of genotype effects such that normal metabolism becomes the risk variant by young adulthood, as has been reliably reported in older smokers.